Assessing the attitudes of Dominican primary school teachers toward the integration of ICT in the classroom - Rolle-Greenidge, Gail; Walcott, Paul (Education Resources Information Center (ERIC), 2020)
Many teachers in developed countries have integrated the use of computers into their classrooms; however, the digital divide has limited this integration in developing countries such as those in the Caribbean. Through a combination of questionnaires and interviews, Dominican primary school teachers' attitudes toward computers; their computer-based activities; and the challenges that reduced the frequency of computer use in their classrooms; were queried. Significant differences in computer enjoyment and computer anxiety between young and mature teachers were reported. Although teachers were willing to use computers in their classrooms, challenges such as alack of resources, limited support and insufficient training prevented more extensive use. Nevertheless, teachers were able to create tests and presentations using word processing and presentation software. This research improves the understanding of teachers’ attitudes toward technology in developing countries and recommends strategies to overcome barriers to classroom technology integration.
Keywords: teachers’ attitudes; information and communication technology; digital divide; Dominican primary schools; millennials